Literary exhaustion and replenishmnet in selected works by Kurt Vonnegut, John Barth and John Irving - Abu Jweid, Abdalhadi Nimer Abdalqader (2015)
This thesis studies the literary exhaustion and its possible replenishment in Kurt Vonnegut’s Slaughterhouse-Five (1969), John Barth’s Chimera (1972), and John Irving’s The World According to Garp (1978). The study mainly focuses on the postmodern experimentation in these novels to critique the spirit of literary exhaustion prevailing modern literature. This experimentation lies in manipulating the plot,narrator, and characters’ discourse in order to provide remedial replenishment for such exhaustion. Therefore, a narrative conceptual framework is applied to analyze these literary elements. The dissertation is divided into six chapters and a conclusion. The first chapter introduces the main arguments of the study including the objectives, questions, statement of the problem, significance of the study, and methodology. Chapter two is the literature review. This chapter presents the selected novels within postmodern narrative and how the dissertation’s argument differs from them. The third chapter is the conceptual framework. The selected conceptual framework comprises three narrative categories. The are 1) atricia augh’s elf-reflective devices, imeticvices, and arrative evices, ) rard enette’s levels of the focali ation factor, and 3) ikhail Bakhtin’s mode of the dialogic discourse. Chapter four studies Kurt Vonnegut’s Slaughterhouse-Five. It emphasizes the epresentation of fiction and realit in the novel. It uses augh’s self-reflexive devices, enette’s concept of the extradiegetic narrator, and Bakhtin’s concept of dialogic discourse to accentuate the author’s implied voice in the novel. The fifth chapter tackles the use of augh’s mimetic devices, enette’s concept of the intradiegetic narrator, and Bakhtin’s concept of the dialogic discourse in John Barth’s Chimera. The chapter also approaches the way in which Barth parodies previous literary works to innovate a postmodern parodic pastiche. Chapter six studies John Irving’s The World According to Garp. This chapter emphasizes the authorial self-consciousness in the novel to highlight the author’s critical voice which addresses the issue of literary exhaustion. Thechapter anal sis depends on augh’s narrative devices, enette’s concept of the extradiegetic narrator, and Bakhtin’s concept of the dialogic discourse. Finally, the conclusion sums up the main arguments of the study.